(untitled) (Research, Society and Development, 2024)
The objective of this research was to analyze the agroecology of water in the Nossa Senhora das Graças community, in the municipality of Manacapuru-AM, according to seasonality and to collaborate with the concept of agroecology, taking into account floodplain areas. The methodology used in this research was the deductive method; As for the means, the research was bibliographic; As for the purposes, the research was qualitative. It was concluded that agroecology is indeed scientific knowledge and that ethnoknowledge, based on the validation of the knowledge of local populations, becomes scientific knowledge. When suggesting this contribution to the concept of agroecology, we assume that the concepts of agroecology presented by the scientific community meet the needs and specificities of each territory and ecosystem. However, the concept of agroecology for the world of water and the Amazon in the conception of this author who writes to you has not been perceptible, clear and evident and even explicit until the present moment.